PWE-035 HDCE using 0.03% versus 0.2% indigocarmine for detecting dysplasia in IBD colitis surveillance. RCT interim-analysis. (8th June 2018) - Lord, Richard; Burr, Nick; Mohammed, Noor; Subramanian, Venkat
Abstract : Introduction: Patients with ulcerative colitis (UC) and Crohn's colitis are known to have an increased risk of colorectal cancer compared with that of the background population. The recent SCENIC consensus statement endorses high definition chromoendoscopy (HDCE) with targeted biopsies for dysplasia detection but required more evidence regarding optimal dye concentrations and mode of delivery. No trials have previously studied this. Our aim was to compare 0.2% indigo carmine (IC) using a spray catheter with that of 0.03% IC via a foot pump, for dysplasia detection in patients undergoing surveillance in IBD colitis. Method: A parallel group randomised controlled trial (ClinicalTrials.gov ID: NCT03250780 ) in which patients undergoing surveillance endoscopy for IBD colitis were randomised into either HDCE using 0.2% IC using a spray catheter or HDCE using 0.03% IC via a foot pump. HD scopes (Olympus CF-HQ290L) and processors (Elite CV 290) were used. Two expert GI histopathologists confirmed presence of dysplasia. Time of withdrawal and ampoules of IC were also recorded. Results: There were 75 patients in each arm (total n=150). Baseline characteristics including colitis phenotype, disease duration, BSG risk category, number of biopsies, concomitant PSC and previous dysplasia were similar in both arms. Dysplasia within the colitic area was found in 12 patients (16.0%) in the 0.2% IC group and 13 patients (17.3%) within the 0.03% IC group, p=0.666 (table 1). Withdrawal was significantly (p<0.001) quicker in the 0.03% IC group (16.36±5.92, 95% CI 14.9–17.7) than in the 0.2% IC group (21.23±6.69, 95% CI 19.7–22.8). The 0.03% IC group used significantly less IC ampoules (2, IQR 2–3) compared with 0.2% IC group (5, IQR 4–5.25), p<0.001. Dysplasia on random biopsies only, was found in 3.3% (n=5) of the cohort. Univariate analysis for dysplasia on random biopsies showed association with BSG high-risk category group (p<0.001), concomitant PSC (p=0.033) and having previous dysplasia (p<0.001). Conclusion: There is no significant difference in dysplasia detection between 0.2% and 0.03% IC concentration. 0.03% IC seems to be on average 5 min quicker and uses less ampoules of IC. There maybe still a place for random biopsies in patients defined by the BSG as high-risk.